ANALYSIS OF LODGING DISTRIBUTION STUDENTS AT MAIN CAMPUS OF UNIVERSITAS NEGERI PADANG - Akbar Ramanda; Dhanu Sekarjati (Universitas Negeri Padang, 2021)
This study aims to determine the distribution of boarding and lodging for students at Universitas Negeri Padang. The research method using descriptive quantitative. The data collection technique used Random Sampling, namely by distributing questionnaires to students by online. The data used are primary data in the form of coordinates for the location of boarding houses, prices and available facilities and secondary data in the form of administrative maps of Padang City. The results of this study obtained student boarding and lodging locations based on location, price and facilities presented in the form of maps and webGIS using Geographic Information Systems. In addition, it is known that on average, Universitas Negeri Padang students choose boarding houses with moderate price classifications ranging from Rp. 250,000-Rp. 400,000 and most are spread around Cendrawasih Street.